Pondok Pesantren Thawalib Padang Tahun 1998-2020 - siti raudatun niswah; Erniwati Erniwati (Jurusan Sejarah FIS UNP, 2021)
Abstract This article is a historical study that discusses the Thawalib Padang Islamic Boarding School in 1998-2020 the purpose of this article is to describe the development of the Thawalib Padang Islamic boarding school in 1998-2020 which is a private school that has experienced several displacements so that the educational process carried out in Islamic schools experienced a very slow process This article uses historical sources, from the process of source documents obtained from Thawalib Padang, interview with the chairman of the thawalib Padang Islamic boarding school, management of students and society. The results of this article explain that the Thawalib Padang Islamic Boarding Scholl was founded by the Thawalib in 1998 because this year the Islamic Boarding School experienced problems on land which resulted in the contstruction of the Islamic Boarding School being slow to build and the teaching and learning process was delayed. In 2000 this Islamic boarding school began to experience development due to the education process that had been running smoothly and adequate educational facilities and developed teacher performance so that it was able to increase students’ learning motivation, thus producing students who excel, such as getting a national level MTQ champion in the city Padang. Keywords: Thawalib, Boarding School, and Development Abstrak Artikel ini merupakan kajian sejarah yang membahas tentang Pondok Pesantren Thawalib Padang tahun 1998-2020. Tujuan artikel ini untuk mendeskripsikan perkembangan pondok pesantren Thawalib Padang tahun 1998-2020 yang merupakan sekolah swasta yang pernah mengalami beberapa kali perpindahan tempat sehingga proses pendidikan yang dilakukan di pondok pesantren mengalami proses yang sangat lambat. Artikel ini menggunakan sumber melalui metode sejarah, dari proses dokumen sumber yang didapatkan dari arsip pesantren Thawalib Padang, wawancara dengan ketua yayasan pondok pesantren Thawalib Padang, pengelolaan peserta didik dan masyarakat. Hasil dari artikel ini menjelaskan bahwa pondok pesantren Thawalib Padang didirikan oleh pihak yayasan pesantren Thawalib pada tahun 1998 karena di tahun ini pondok pesantren mengalami permasalahan sengketa tanah yang mengakibatkan bangunan pondok pesantren lambat dibangun sehingga proses kegiatan belajar-mengajar tertunda. Tahun 2000 pondok pesantren ini mulai mengalami perkembangan dikarenakan proses pendidikan yang sudah berjalan lancar serta fasilitas pendidikan yang sudah memadai dan mengembangkan kinerja guru sehingga mampu meningkatkan motivasi belajar peserta didik, sehingga menghasilkan peserta didik yang berprestasi seperti salah mendapatkan juara MTQ Tingkat Nasional di Kota Padang. Kata Kunci: Thawalib, Pesantren, dan Perkembangan